2019
DOI: 10.1002/hbm.24899
|View full text |Cite
|
Sign up to set email alerts
|

Improved prediction of brain age using multimodal neuroimaging data

Abstract: Brain age prediction based on imaging data and machine learning (ML) methods has great potential to provide insights into the development of cognition and mental disorders. Though different ML models have been proposed, a systematic comparison of ML models in combination with imaging features derived from different modalities is still needed. In this study, we evaluate the prediction performance of 36 combinations of imaging features and ML models including deep learning. We utilize single and multimodal brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
117
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(125 citation statements)
references
References 67 publications
7
117
1
Order By: Relevance
“…Despite poorer performance accuracy of the functional connectivity model, the fMRIbased brain-age deltas showed associations with the biomedical variables that were similar to the other modalities. In line with recent findings from UK Biobank [14,15], positive associations were found between brain-age deltas and diastolic blood pressure, alcohol intake, and stroke risk, concurring with previous WHII studies [32,50], and demonstrating that the brain age-delta measure reflects individual variation in neural aging processes [30]. The associations with biomedical variables were consistent across models (see Figure 5), indicating that while modality-specific brain age models may be informative in patient groups where tissue types are differently affected by disease [26,27,54,67,68], such models may be more closely related in healthy cohorts [14].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Despite poorer performance accuracy of the functional connectivity model, the fMRIbased brain-age deltas showed associations with the biomedical variables that were similar to the other modalities. In line with recent findings from UK Biobank [14,15], positive associations were found between brain-age deltas and diastolic blood pressure, alcohol intake, and stroke risk, concurring with previous WHII studies [32,50], and demonstrating that the brain age-delta measure reflects individual variation in neural aging processes [30]. The associations with biomedical variables were consistent across models (see Figure 5), indicating that while modality-specific brain age models may be informative in patient groups where tissue types are differently affected by disease [26,27,54,67,68], such models may be more closely related in healthy cohorts [14].…”
Section: Discussionsupporting
confidence: 91%
“…Although previous studies have suggested better prediction with multiple imaging modalities [13,14,30,54], the current study showed equivalent prediction accuracy between the multimodal model and the gray and white matter models. The exclusion of low-quality data improved the performance of the multimodal model, suggesting that established procedures for data quality control may have implications for model performance [39,55].…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations